Antasenden Dari Task Performance Karyawan Perbankan di Jakarta - Sahnaz Sakinah; Dita Oki Berliyanti; Wiwik Robiatul Adawiyah (J-MAS (Jurnal Manajemen dan Sains), 2023)
The banking world is one of the important aspects in the financial sustainability of society so that the need for optimal task performance from employees in order to provide optimal service to customers. Employee task performance can be influenced by several factors such as autonomous motivation, organizational citizenship behavior, educational level and innovative work. This study aims to analyze the influence of organizational citizenship behavior, autonomous motivation, educational level, and innovative work on task performance in 201 employees of PT Mandiri (Persero) Tbk. Determination of the sample in this study is Non-Probability Sampling with saturated sampling technique or census. Data collection was carried out by questionnaires distributed to respondents via google form. The data analysis technique was carried out using multiple linear regression analysis. The results of data analysis show that autonomous motivation, organizational citizenship behavior, educational level and innovative work have a significant positive influence on employee task performance. Managerial implications in this study are expected that companies in recruiting employees pay more attention to factors that can affect employee performance in the future.